Obesity accelerates endothelial-to-mesenchymal transition in adipose tissues of mice and humans - Chavkin, Nicholas W.; Vippa, Tanvi; Jung, Changhee; McDonnell, Stephanie; Hirschi, Karen K.; Gokce, Noyan; Walsh, Kenneth (Frontiers in Cardiovascular Medicine, 2023)
Introduction Vascular dysfunction and chronic inflammation are characteristics of obesity-induced adipose tissue dysfunction. Proinflammatory cytokines can drive an endothelial-to-mesenchymal transition (EndoMT), where endothelial cells undergo a phenotypic switch to mesenchymal-like cells that are pro-inflammatory and pro-fibrotic. In this study, we sought to determine whether obesity can promote EndoMT in adipose tissue. Methods Mice in which endothelial cells are lineage-traced with eYFP were fed a high-fat/high-sucrose (HF/HS) or Control diet for 13, 26, and 52 weeks, and EndoMT was assessed in adipose tissue depots as percentage of CD45−CD31−Acta2+ mesenchymal-like cells that were eYFP +. EndoMT was also assessed in human adipose endothelial cells through cell culture assays and by the analysis of single cell RNA sequencing datasets obtained from the visceral adipose tissues of obese individuals. Results Quantification by flow cytometry showed that mice fed a HF/HS diet display a time-dependent increase in EndoMT over Control diet in subcutaneous adipose tissue (+3.0%, +2.6-fold at 13 weeks; +10.6%, +3.2-fold at 26 weeks; +11.8%, +2.9-fold at 52 weeks) and visceral adipose tissue (+5.5%, +2.3-fold at 13 weeks; +20.7%, +4.3-fold at 26 weeks; +25.7%, +4.8-fold at 52 weeks). Transcriptomic analysis revealed that EndoMT cells in visceral adipose tissue have enriched expression of genes associated with inflammatory and TGFβ signaling pathways. Human adipose-derived microvascular endothelial cells cultured with TGF-β1, IFN-γ, and TNF-α exhibited a similar upregulation of EndoMT markers and induction of inflammatory response pathways. Analysis of single cell RNA sequencing datasets from visceral adipose tissue of obese patients revealed a nascent EndoMT sub-cluster of endothelial cells with reduced PECAM1 and increased ACTA2 expression, which was also enriched for inflammatory signaling genes and other genes associated with EndoMT. Discussion These experimental and clinical findings show that chronic obesity can accelerate EndoMT in adipose tissue. We speculate that EndoMT is a feature of adipose tissue dysfunction that contributes to local inflammation and the systemic metabolic effects of obesity..